Physiotherapy clinical teachers' perceptions on important attributes in teaching – A Nigerian perspective. (March 2013) - Oyeyemi, Adetoyeje Y.; Oyeyemi, Adewale L.; Adegoke, Babatunde O.; Rufai, Adamu A.
Abstract: Aim : The objective of this study was to investigate Nigerian physiotherapy teachers' self-assessment on the attributes of effective clinical teaching and the importance attached to these attributes. Methodology: The McGill Clinical Teacher Evaluation including self-assessment and importance of the attributes of clinical teaching was used to survey 46 clinicians and academicians who teach physiotherapy in five of the seven physiotherapy programs in Nigeria. Descriptive and non-parametric statistics were used to analyze and interpret data. Results : Overall, the Nigerian teachers' self- and importance rating on McGill clinical teachers' attributes was high. The teachers rated themselves least on attributes related to challenging content from text and journals and encouraging student to take responsibility for their learning, while customizing clinical teaching to suit the students' level and occasionally challenging content from texts and journals were the least important attributes. Academic faculty gave higher importance ratings for displaying good judgment in decision making than clinical faculty, while a modest link was found between years of post-professional experience and self-perception as effective teacher. Conclusion : The attributes with lowest self-assessment and importance may indicate areas for future concentration particularly in the Nigerian academic community, including curriculum content and design of physiotherapy teachers training.